A report on learning gains and student confidence after incorporating an enzyme purification and characterization course‐based undergraduate experience. Issue 2 (9th December 2022) - Jones, Eric; Glanz, Hunter; Wilkinson, Steven; Fogle, Emily
Abstract: Course‐based undergraduate research experiences (CUREs) can provide undergraduate students access to research opportunities when student and faculty resources are limited. In addition to expanding research opportunities, CUREs may also be explored as a pedagogical tool for improving student learning of course content and laboratory skills, as well as improving meta‐cognitive features such as confidence. We examined how a 6‐week CURE in an upper‐level undergraduate biochemistry lab affected student gains in content knowledge and confidence in scientific abilities, compared to a non‐CURE section of the same course. We find that gains in content knowledge were similar between CURE and non‐CURE sections, indicating the CURE does not negatively impact student learning. The CURE was associated with a statistically significant gain in student confidence, compared to non‐CURE group. These results show that even a relatively short CURE can be effective in improving student confidence at scientific research skills, in addition to expanding access to research.